PROGRAM SENTONO MENABUNG - Jamalul Lail (Asian Journal of Innovation and Entrepreneurship, 2015)
Attitude fond of saving needs to be instilled in children from an early age to avoid the behavior of shoppers. The author tried to instill awareness fond of saving onchildren of Sentono village with variety of interesting wayss named Sentono SavingsProgram. Children are expected to remain consistent saving although the programfinished running.